Polish economic miracle as a factor of the socialist system of economy collapse - Chebotarov, V.; Chebotarov, Ye. (Економічний вісник Донбасу, 2016)
The definition of "the Polish economic miracle" concept as a scientific category is provided in the history of science for the first time. The essential features of a given category, the epistemological basis of its knowledge and quantification tool are classified in this article. Also the institutional of Polish economic miracle are considered. Its comparative analysis with similar phenomena and processes in Germany, Japan and Singapore is held. The role of Polish economic miracle in the collapse of the socialist system it clarifies. Вперше в історії науки дається визначення поняття «польське економічне диво» як наукової категорії. Класифікуються сутнісні риси даної категорії, гносеологічні основи її пізнання та інструментарій кількісної оцінки. Розглядаються інституціональні передумови польського економічного дива. Проводиться його порівняльний аналіз із аналогічними явищами й процесами в ФРН, Японії та Сінгапурі. Усвідомлюється роль польського економічного дива в саморозпаді соціалістичної системи. Впервые в истории науки дается определение понятия «польское экономическое чудо» как научной категории. Классифицируются сущностные черты данной категории, гносеологические основы ее познания и инструментарий количественной оценки. Рассматриваются институциональные предпосылки польского экономического чуда. Проводится его сравнительный анализ с аналогичными явлениями и процессами в ФРГ, Японии и Сингапуре. Уясняется роль польского экономического чуда в крахе социалистической системы.